Notas sobre la flora del Parque Nacional Marítimo-Terrestre de las Islas Atlánticas de Galicia. - Blanco-Dios, Jaime B. (Acta Botanica Malacitana, 2008)
Notes about the flora of the National Maritime-Terrestrial Park of the Atlantic Islands of Galicia. Key words. Flora, chorology, Cies, Sálvora, National Park, Galicia, Spain Palabras clave. Flora, corología, Cies, Sálvora, Parque Nacional, Galicia, España